(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The paper illustrates the relevance of the segment of small merchants active in the ambrosian metropolis between the end of the 14th and the beginning of the 15th century. Through the analysis of a substantial nucleus of notarial deeds, the intense relationship between the operators of the countryside and Milan emerges powerfully, in a close network of businesses with different economic consistency. The expansion of the city economy, supported by the political one, which characterizes this period, is sustained by the spread of commercial activities at different levels. In this context the strength of small merchants develops and consolidates, becoming a crucial part of the whole class.